2015
DOI: 10.1155/2015/564087
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Nanofibrous Polymer Scaffolds for Cartilage Tissue Engineering

Abstract: Polymer substrates obtained from poly(lactic acid) (PLA) nanofibres modified with carbon nanotubes (CNTs) and gelatin (GEL) for cartilage tissue engineering are studied. The work presents the results of physical, mechanical, and biological assessment. The hybrid structure of PLA and gelatine nanofibres, carbon nanotubes- (CNTs-) modified PLA nanofibres, and pure PLA-based nanofibres was manufactured in the form of fibrous membranes. The fibrous samples with different microstructures were obtained by electrospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
1
15
0
1
Order By: Relevance
“…The medium with pure PLA nonwoven (mat) served as a control sample (PLA). Biocompatibility of this material has been confirmed in previous studies of the authors [24].…”
Section: Cell Culture Experimentssupporting
confidence: 77%
See 4 more Smart Citations
“…The medium with pure PLA nonwoven (mat) served as a control sample (PLA). Biocompatibility of this material has been confirmed in previous studies of the authors [24].…”
Section: Cell Culture Experimentssupporting
confidence: 77%
“…The exposed CNT can induce regenerative processes, depending on the intended use, in bone, nervous, or cartilage tissue. In addition, polymeric fibrous scaffolds with a specific orientation of nanofibres may favour directional cell growth [24,46]. The biological test showed that the nanofibres containing the carbon nanotubes were not toxic.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations